Pengaruh Aplikasi Larutan Daun Jeruk Nipis (Citrus aurantiifolia) Pada Walang Sangit Di Kapuas Murung Kalimantan Tengah - Mariana, Mariana; Pramudi, Muhammad Indar; Liestiany, Elly (JURNAL PROTEKSI TANAMAN TROPIKA, 2024)
Walang sangit (Leptocorisa oratorius Fabricius, (Hemiptera:Alydidae); syn. Leptocorisa acuta) are one of the rice pests that can cause problems because they can reduce the quantity and quality of production, so these grasshoppers need to be controlled. Controlling stink bugs using chemicals is currently more popular because they are quickly visible. However, long-term use of chemicals is not good. Therefore, an alternative method of controlling stink bugs is needed using a solution of lime leaves (Citrus aurantiifolia). This research aims to determine lime leaf solution in controlling stink bugs. The research design used was a Completely Randomized Design (CRD) 1 factor consisting of 6 treatments and 4 replications, namely with doses of PO (control), PA (20g/80 ml), PB (22.5g/77.5 ml), PC (25g/75 ml), PD (27.5g/72.5 ml) and PE (30g/70 ml). The results of the research show that lime solution can be used as a natural pesticide because it has an effect on suppressing the death of the stink bug. The best dose that can kill the stink bug is 30g/70 ml lime leaf solution.